Recent developments in the role and design of social protection programmes: A policy dialogue, expert workshop and south-south learning event - Fábio Veras Soares; Radhika Lal; Ryan Higgitt (International Policy Centre for Inclusive Growth (IPC-IG), 2013)
This issue of Poverty in Focus brings a set of articles that discuss some of the recent developments and innovations in the social protection area in developing countries. Most invited authors were presenters at the Policy Dialogue, Expert Workshop and South-South Learning Event organised by IPC-IG with the support of AusAID, the Secretariat of Strategic Affairs and the Institute for Applied Economic Research of the Brazilian Government in December 2012. The workshop was an opportunity to bring together policymakers, researchers and practitioners from developing countries as well as representatives from different multilateral organisations to discuss social protection innovations from three perspectives: a) an informative perspective to foster and support the dialogue and cooperation between policymakers from different countries; b) an analytical perspective focusing on the evidence of the impact of social protection programmes; and c) a learning perspective in which researchers and policymakers could strengthen the learning process and share their thoughts on the knowledge gaps in this area. [...]
Keywords: 330